Expand and simplify.

a) 5(3x-1)+4(x^2-3x+3)(x+6)

### 1 Answer | Add Yours

Expand and simplify `5(3x-1)+4(x^2-3x+3)(x+6)` :

First we get rid of grouping symbols by using the distributive property:

`5(3x-1)+4(x^2-3x+3)(x+6)`

`=> 15x-5+4[x^3+6x^2-3x^2-18x+3x+18]` Collect like terms:

`=>15x-5+4[x^3+3x^2-15x+18]`

`=>15x-5+4x^3+12x^2-60x+72` Collect like terms:

`=>4x^3+12x^2-45x+67`

**Thus the required answer is** `4x^3+12x^2-45x+67`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes